The Speaker Identification Ability of Blind and Sighted Listeners An Empirical Investigation - Braun, Almut (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2016)
Almut Braun carried out forensic phonetic speaker identification experiments (voice lineups) with 306 lay listeners. Blind listeners significantly outperformed sighted listeners when the speech recordings were presented in studio quality. For recordings in mobile phone quality or of whispering voices, blind and sighted listeners achieved similar results. The data can be used as reference material for real cases with blind earwitnesses. Furthermore, it is discussed whether blind individuals are particularly suitable to work as forensic audio analysts for law enforcement agencies. The Contents Forensic speaker identification/speaker recognition Earwitness memory of blind and sighted listeners Blind listeners' auditory abilities and sensory compensation Parameters which influence listeners' speaker identification abilities Issues to consider when creating a forensic phonetic voice lineup / voice parade< Target Groups Researchers and students in the field of (forensic) Phonetics, Psychology (person/voice recognition) and Law Forensic Phoneticians/Speech Scientists, staff of Criminal Police Offices, members of the International Association for Forensic Phonetics and Acoustics The Author Almut Braun was a doctoral candidate in the Department of Phonetics at Philipps-Universität Marburg, Germany. She works currently as a Research Associate in the Department of Language and Linguistic Science at the University of York, UK.